2017
DOI: 10.2217/pgs-2016-0175
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Feasibility of Delivering Pharmacogenetic Testing in a Community Pharmacy Setting

Abstract: Aim:To describe the rationale and design of a study evaluating the delivery of pharmacogenetic (PGx) testing in community pharmacies. Study rationale: Pharmacists have expressed interest in offering PGx testing; however, their lack of knowledge and experience, patients' acceptance and feasibility are unknown in this setting. Study design: Through a cluster randomized trial, we will assess pharmacist and patient experiences with delivery of PGx testing as a standalone service or integrated into medication thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Details of this study design have been previously described. 26 In summary, a cluster randomized trial was conducted whereby independent community pharmacies were randomized to provide PGx testing or PGx testing with MTM. Buccal swab samples were collected from patients at the pharmacy who presented with a new or recent prescription for one of 10 drugs for which PGx recommendations are available and sent to Pathway Genomics for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Details of this study design have been previously described. 26 In summary, a cluster randomized trial was conducted whereby independent community pharmacies were randomized to provide PGx testing or PGx testing with MTM. Buccal swab samples were collected from patients at the pharmacy who presented with a new or recent prescription for one of 10 drugs for which PGx recommendations are available and sent to Pathway Genomics for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, community-based pharmacist practitioners have become involved in POCT for infectious diseases like Human Immunodeficiency Virus (HIV), Hepatitis C, streptococcus, and influenza [44,45]. As pharmacogenomics develops, POCT devices that measure drug metabolism are becoming available and community-based pharmacist practitioners with their drug expertise are a good choice to provide this service [46]. This would prevent someone from taking a medication that they cannot process and avoid having to try multiple medications to find the right one.…”
Section: Resultsmentioning
confidence: 99%
“…These questions, among others, led to the advocacy for and development of community pharmacy-based models for PGx-focused management of clopidogrel following release of the associated CPIC and other guidelines. [41][42][43][44][45][49][50][51][70][71][72] For personal use only.…”
Section: Clopidogrel Pgx and Community Pharmacy Models Published Modelsmentioning
confidence: 99%
“…41,42 However, recent studies have demonstrated the viability of PGx work in general in community pharmacies. [43][44][45] Further, DTC PGx testing presents new opportunities for community pharmacists to be deeply involved in DTC PGx work. 46 As DTC PGx testing becomes increasingly available, cost efficient, and visible in health systems and community pharmacies, clinical workflow models may need to further adapt to involve patient-gathered PGx data.…”
Section: Introduction and Background Of Pharmacogenomics Across Health-care Settingsmentioning
confidence: 99%